Study On Fusion Infrared (IR) And Visible Images For Face Recognition - Mat Desa, Shahbe (2008)
This study begins with the single modality based recognition using IR and visible images. The investigation is carried out by considering different methodologies of low dimensional face subspaces. Generally, linear based approaches are not as efficient as nonlinear method in handling the different appearances of face images.